G-helix of Maspin Mediates Effects on Cell Migration and Adhesion - Ravenhill, Lorna (American Society for Biochemistry and Molecular Biology, 2010)
Maspin is a member of the serine protease inhibitor (serpin) superfamily that lacks protease inhibitory ability, although displaying tumor metastasis-suppressing activity resulting from its influence on cell migration, invasion, proliferation, apoptosis, and adhesion. The molecular mechanisms of these actions of maspin are as yet undefined. Here, we sought to identify critical functional motifs by the expression of maspin with point mutations at sites potentially involved in protein-protein interactions: the G α-helix (G-helix), an internal salt bridge or the P1 position of the reactive center loop. Our findings indicate that only mutations in the G-helix attenuated inhibition of cell migration by maspin and that this structural element is also involved in the effect of maspin on cell adhesion. The action of maspin on cell migration could be mimicked by a 15-mer G-helix peptide, indicating that the G-helix is both essential and sufficient for this effect. In addition, we provide evidence that the effects of the G-helix of maspin are dependent on β1 integrins. These data reveal that the major extracellular functions associated with the tumor suppressive action of maspin likely involve interactions in which the G-helix plays a key role.